Assistance with MSME Financial Reporting at The Mushroom Farmers Group Preserve Batok Village Bali - Banten Province - Neneng Sri Suprihatin; Lulu Nailufaroh (EQUATOR SINAR AKADEMIA, 2023)
One of the problems faced by partners are low mushroom production capacity, using conventional marketing methods for sales, not keeping proper financial records so that partners do not know the actual profit. The solutions offered to partners are as follows: a) increasing mushroom production capacity by providing appropriate technological tools and facilities, such as backlog press machines and autoclaves; b) providing training on recording financial transactions using the web use an application for recording financial information for micro and small businesses (SI APIK) application issued by Bank Indonesia, which will assist partners in recording their financial transactions and enable them to Empower sustainable farmer group partners to become independent communities is the outcome goal of this service. After empowering the external partners, the results are as follows: a) Increased mushroom production capacity and b) improved partner financial recording. Increasing partners' ability to manage finances is proof of success.